Eksperimen Dengan Media Tulang Sapi Sebagai Media Alternatif Produk Interior - Jonathan Adrianto; Andereas Pandu Setiawan; Frenky Tanaya (Intra, 2019)
Cow bone is a material that is very close to our daily life. The material is used for animals to consume and humans for many life factors. The abundant availability is caused by beef being considered one of the main commodities. Through this fact, the researcher wants to explore the potential of cow bones which can provide aesthetic values and is potential to be developed. By using the experimental research method that starts from formulating problems until the implementation stage which consists of dependent variables which are cow bones, along with the independent variables which are durability tests, adhesive power, and odor dissipating media. The final result is a wall panel which presents the utilization of color gradations, textures, and also some compositions of other types of materials.